Diagnostik Kesulitan Belajar dan Perilaku Bermasalah Siswa - Solmeriana Sinaga; Fredik Melkias Boiliu; Yunardi Kristian Zega; Rini Sumanti Sapalakkai (REAL DIDACHE: Journal of Christian Education, 2023)
This research aims to analyze students' learning difficulties and problematic behaviors in learning Christian religious education in schools. Student learning difficulties and problematic behavior in learning are causative factors that hinder the teaching and learning process so that it does not achieve predetermined goals. Therefore, teachers of Christian religious education must diagnose students to identify any problems experienced in them. This will help teachers so that the teaching and learning process is adjusted to existing situations and conditions or needs. For this reason, the research uses descriptive qualitative methods using secondary data, namely data collection referring to scientific articles and books related to this discussion. The results in this research will analyze the factors causing students' learning difficulties and problematic behavior in learning Christian religious education. In addition, the role of Christian religious education teachers in dealing with student learning difficulties and problematic behaviors in Christian religious education.Keywords: learning difficulties; Christian religious education; problematic behavior AbstrakPenelitian ini bertujuan untuk menganalisis kesulitan belajar siswa dan perilaku bermasalah dalam pembelajaran pendidikan agama Kristen di sekolah. Kesulitan belajar siswa dan perilaku bermasalah dalam belajar merupakan faktor penyebab yang menghambat proses belajar mengajar sehingga tidak mencapai tujuan yang telah ditentukan. Oleh sebab itu, guru pendidikan agama Kristen harus mendiagnosis siswa untuk mengidentifikasi setiap permasalah yang dialami dalam dirinya. Hal ini akan menolong guru sehingga dalam proses belajar mengajar disesuaikan dengan situasi dan kondisi atau kebutuhan yang ada. Untuk itu, penelitian menggunakan metode kualitatif deskriptif dengan menggunakan data sekunder yakni pengambilan data merujuk pada artikel-artikel ilmiah dan buku-buku yang berkaitan dengan pembahasan ini. Hasil dalam penelitian ini akan menganalisis faktor penyebab kesulitan belajar siswa dan perilaku bermasalah dalam belajar pendidikan agama Kristen. Selain itu, peran guru pendidikan agama Kristen dalam menghadapi kesulitan belajar siswa dan perilaku bermasalah dalam pendidikan agama Kristen.Kata Kunci: kesulitan belajar; pendidikan agama kristen; perilaku bermasalah